Buckling of joined composite conical shells using shear deformation theory under axial compression - Izadi, Mohammad Hadi (Strojniški vestnik, 2019)
This paper investigates critical buckling loads in joined conical shells under axial compression. An analytical approach has been applied to study classical linear buckling of joined cones that are made of cross-ply fiber reinforced laminates. The governing equations have been extracted using first-order shear deformation theory (FSDT), and an analytical solution has been applied to extract critical buckling loads. Accordingly, the system of partial differential equations has been solved via separation of variables using Fourier expansion and power series method. The effects of the number of layers, lamination sequences, semi-vertex angles, shell thicknesses, shell lengths and boundary conditions on the stability of joined cones have been examined. For validation, the specific examples of the present study have been compared to previous studies. Using ABAQUSE/CAE software (a FEM-based software), the results of finite element have been extracted. The present method is in good agreement with the finite element and other research results. Finally, the differences in classical shell theory (CST) of Donnell type and first-order shear deformation theory have been discussed for different shell thicknesses.
Keywords: aksialni tlak; buckling; first-order shear deformation; joined laminated conical shell; križna laminacija; metoda končnih elementov; potenčna vrsta; power series; spojena laminirana konična lupina; strižna deformacija prvega reda; uklon